2018 IEEE Conference on Decision and Control (CDC) 2018
DOI: 10.1109/cdc.2018.8619707
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Critical Density of Road Transportation Networks using Infinitesimal Perturbation Analysis of Hybrid Systems

Abstract: Traffic congestion can be eliminated by restraining the number of vehicles within an urban region to be below its critical density. To achieve that, [1], [2] proposed a route-reservation architecture that makes appropriate routing schedules according to a region's critical density, and controls vehicle departure times, so that vehicles arrive at their destination in the earliest possible time while avoiding roadsegments that are expected to be at their critical density. However, the critical density is not alw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…If no reservation section exists on path r, then ε ue,w r � 1; otherwise, ε ue,w r � 0. Equation (15) ensures that the sum of all path fows through link a is equal to q ue a . δ ue,w a,r are path-link relations.…”
Section: Bilevel Programming Model Based On Orv Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…If no reservation section exists on path r, then ε ue,w r � 1; otherwise, ε ue,w r � 0. Equation (15) ensures that the sum of all path fows through link a is equal to q ue a . δ ue,w a,r are path-link relations.…”
Section: Bilevel Programming Model Based On Orv Constraintsmentioning
confidence: 99%
“…Terefore, in recent years, scholars have preferred to mine trafc fow data to determine reservation volumes [14]. Menelaou et al [15] replaced the capacity constraint with the density constraint and used infnitesimal perturbation analysis to capture the dynamic change in the critical density value. By comparing the estimated capacity and critical density distribution function, Geistefeldt and Shojaat [16] showed that the relative variability of the capacity is lower than that of the critical density.…”
Section: Introductionmentioning
confidence: 99%